Banglalink Digital Communications Limited: re-engineering & process development of base transceiver station (BTS) rent database and service users satisfaction level of m-banking - Arefin, Md. Samiul (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2015.